Working in women's archives : researching women's private literature and archival documents - Buss, Helen M.; Kadar, Marlene, 1950- (Life writing series., 2001)
"What Comes to mind when we hear that a friend or colleague is studying unpublished documents in a celebrated author's archive? We might assume that they are reading factual documents or, at the very least, straightforward accounts of the truth about someone or some event. But are they?" "Working in Women's Archives is a collection of essays that poses this question and offers a variety of answers. Any assumption readers may have about the archive as a neutral library space or about the archival document as a simple and pure text is challenged." "In essays discussing celebrated Canadian authors such as Marian Engel and L.M. Montgomery, as well as lesser-known writers such as Constance Kerr Sissons and Marie Rose Smith, Working in Women's Archives persuades us that our research methods must be revised and refined in order to create a scholarly place for a greater variety of archival subjects and to accurately represent them in current feminist and poststructuralist theories."--Jacket